Coordination and Three-Stage Supply Chain Optimization of Agricultural Products in Bangladesh Under Uncertainties - Islam, Mohammad Khairul; Alam, Md. Mahmud; Uddin, Mohammed Forhad; Faruque, Gazi Mohammad Omar (International Journal of Supply Chain Management, 2020)
Abstract- In this study presents three stage supply chain network (SCN) coordination and profit optimization of agricultural products considering several uncertainties. Most of the agricultural products are in general cost expensive with high risk in probability due to its fluctuating prices. To developed a Mixed Integer Linear Programming (MILP) model and analyze the situation of insufficient production capacity for the producer as the reason for shortages. In this study to investigated supply chain network (SCN) are two distinct freelance supply organizations. SCN management has the difficulties for the disconnected and freelance economic people. Further, fast technological changes and high fight build SCN a lot of complicated. The problem of locating distribution centers (DCs) is one among the foremost necessary problems in design of SCN. The models are applied to a real case of optimization the profit before and after coordination and also to analyze the sensitivity under demand and cost uncertainty. The MILP models consider the facilities are coordinated by mutually sharing information with each other among producer, retailer and distributor. The formulated MILP model is solved by using a mathematical programming language (AMPL) and results obtained by appropriate solver MINOS. Numerical example with the sensitivity of various parameters has been deployed to validate the models. Results show that after coordination, the individual profits could be increased without any extra investment.